THE IMPORTANCE OF INNOVATIVE METHODS IN STRATEGIC MANAGEMENT OF ENTERPRISES - Shirinova Shahnoza Abdinabiyevna; Fayzullayeva Xalima Faxriddinovna (Web of Journals Publishing, 2025)
This article examines the role and importance of innovative approaches in the strategic management of companies. It emphasizes that “innovation” encompasses not only technical inventions or scientific discoveries, but also the introduction of new methods in management, marketing, and organizational structures. Drawing on classic strategic management theories (Igor Ansoff, Michael Porter, Henry Mintzberg) and contemporary innovation management methodologies (Design Thinking, Lean Startup, Agile), the article demonstrates how combining these perspectives can boost competitiveness, ensure sustainable economic growth, and facilitate rapid adaptation in today’s dynamic market environment. The paper explores practical considerations such as SWOT, PESTEL analysis, Porter’s strategies, and details the core stages of innovation-oriented strategic management (goal-setting, analysis, strategy selection, implementation, control). It also discusses key indicators for assessing innovation performance, challenges in state-owned enterprises, and offers recommendations for enhancing human capital. The concluding argument underscores that integrating strategic management with innovative practices is a critical factor in achieving corporate success and remaining competitive in a rapidly changing global economy.
Keywords: Strategic management, innovative approaches, competitiveness, management, marketing, organizational structure, R&D (Research and Development), innovation management, SWOT, PESTEL, digital transformation.